CONSTRUCTION OF A QUESTIONNAIRE RELATED TO SOME ASPECTS OF HEALTH CARE FOR RECREATIONAL ATHLETES - Joško Sindik; Narcisa Vojnović (Sport Scientific And Practical Aspects, 2025)
The main objective of this study was to determine latent dimensions of the Questionnaire for recreational athletes and the correlations between variables of daily effort, the importance of free time and motivation to take care of personal health, at the recreational athletes. We examined a sample of 127 recreational athletes, both gender, different age and educational level, practicing for a different period of time in five different sports and recreation centers in Zagreb. We found four latent dimensions in the base of co-variations between the variables of Questionnaire for recreational athletes: the importance of health care, stress and fitness, experience of daily fatigue and the importance of leisure time. There is only one significant correlation between the dimensions of the Questionnaire: health care and the importance of leisure time. There is no significant possibility of prediction for the duration of physical exercising per week, based on the dimensions of the Questionnaire for recreational athletes.